Involvement of the Olfactory Apparatus by Gliomas - Wu, X.; Li, Y.; Glastonbury, C.M.; Cha, S. (American Journal of Neuroradiology, 2020)
SUMMARY: The olfactory bulbs and tracts are central nervous system white matter tracts maintained by central neuroglia. Although rare, gliomas can originate from and progress to involve the olfactory apparatus. Through a Health Insurance Portability and Accountability Act–compliant retrospective review of the institutional teaching files and brain MR imaging reports spanning 10 years, we identified 12 cases of gliomas involving the olfactory bulbs and tracts, including 6 cases of glioblastoma, 2 cases of anaplastic oligodendroglioma, and 1 case each of pilocytic astrocytoma, diffuse (grade II) astrocytoma, anaplastic astrocytoma (grade III), and diffuse midline glioma. All except the pilocytic astrocytoma occurred in patients with known primary glial tumors elsewhere. Imaging findings of olfactory tumor involvement ranged from well-demarcated enhancing masses to ill-defined enhancing infiltrative lesions to nonenhancing masslike FLAIR signal abnormality within the olfactory tracts. Familiarity with the imaging findings of glioma involvement of the olfactory nerves is important for timely diagnosis and treatment of recurrent gliomas and to distinguish them from other disease processes.GBMglioblastoma multiformeTMZtemozolomideEGFRepidermal growth factor receptorIDH1Isocitrate dehydrogenase 1MGMTO6-methylguanine methyltransferase